An examination of frontline employee–customer incidental similarities in service failure and recovery contexts. Issue 6 (3rd March 2023) - Lindsey‐Hall, Kristina K.; Jaramillo, Susana; Baker, Thomas L.; Bachrach, Daniel G.
Abstract: Developing rapport during the "moment of truth" when frontline employees (FLEs) interact with customers has long been an important topic for researchers and managers. We suggest incidental similarities—seemingly trivial shared points of comparison between customers and FLEs—can play a vital role during this juncture in service failure and recovery contexts. Across two experimental studies, we investigate several relationships impacted by the presence or absence of an incidental similarity between FLEs and customers for their effect on satisfaction and repatronage intentions. Results suggest incidental similarities can reduce failure attributions toward service providers and improve these important customer‐related outcomes (study 1). Results of study 2 extend our findings, demonstrating that rapport can serve as a mediating mechanism explaining the relationship between incidental similarities and these key service outcomes. Study 2 also reveals that FLE authenticity acts as a boundary condition of this relationship, accentuating the indirect, conditional relationships between incidental similarities, and satisfaction and repatronage intentions. Critically, we demonstrate that an incidental similarity can be even more effective when there is no recovery. By pointing out the role of incidental similarities in service encounters, our research makes significant contributions to aiding understanding of how rapport can be developed during the relatively brief time customers interact with service employees.